Accounting for account-abilities: Examining the relationships between farm nutrient measurement and collaborative water governance dynamics in Canterbury, New Zealand. (May 2022) - Hale, James; Legun, Katharine; Campbell, Hugh
Abstract: Water quality has become a significant concern for the New Zealand public. The source of its decline in recent years has been largely attributed to the expansion of the dairying industry, and its improvement, a focal point of environmental management. A collaborative model has been developed in the Canterbury region, where committees have been created including government representatives, water management experts, farmers, and non-farming community members. These committees develop water management plans in a water catchment and can be seen to embody a form of socialising accountability where different groups hold each other accountable and share responsibility. One feature of the plans is the establishment of nitrogen loss thresholds for farms in a catchment, implemented through a highly technical form of nutrient modelling. Drawing from interviews and observations in Canterbury water governance networks, we argue that there is a tension between collaborative forms of environmental governance that seeks to socialise accountability, and nutrient modelling that de-socialise accountability in practice. We discuss how these tensions may challenge participatory forms of governance. Highlights: Develops an analytic approach to examine processes of accountability and legitimation in governance practice. Argues there is a tension between collaborative governance that socialises accountability, and modelling that de-socialises accountability. Discusses tensions between individualising processes of accountability and collectivising forms of governance.